Flood in Tripura in October 1958 - CHAUDHURY, A. K. (MAUSAM, 1964)
The paper contains the analysis of the Hydro-meteorological aspects of Hood in the State of Tripura caused by a recurving Bay storm in the month of October 1958 during the retreating phase of the southwest monsoon. From the isohyetal patterns of this storm, it is seen that northern sub-divisions of the State, which were subjected to more inundations received comparatively lesser amount of rainfall. This suggests the higher susceptibility to floodings of the northern groups of rivers, flowing from south to north through the narrow, elongated valleys intersticed between the denuded ranges. Further, from a comparative study, it is seen that under identical orientation of storm tracks, the march of precipitation and its general distribution in Tripura State follow more or less similar patterns.